Deutung und Diskretion. Zum Problem des Biographismus im Fall Bachmann - Frisch - Fliedl, Konstanze (Revista de Filología Alemana, 2002)
The relationship between Max Frisch and Ingeborg Bachmann is extensively documented, and traces of this relationship in the texts of both authors are undeniable. But one should be cautious to not make the positivistic mistake of presuming that writers always write about their own lives – or at least women writers. It is a biographical prejudice that women are not really able to objectify their experiences, to untie oeuvre from life. In this sense, Frisch’s and Bachmann’s story has become a topic of unpleasant gossip. But literary authors themselves have always overtaken such kinds of reductive interpretations: their work produces a project of subjectivity and autobiographical discourse, and rehearses the construction of ego and vita. One’s own autobiographical narration is at heart fictional: this is shown by ‘Gantenbein’, ‘Malina’ and ‘Montauk’. But these texts also make a point that takes us beyond the postmodern «anything goes»: the fact of offensiveness. Here, the most virtual image can deeply strike the real person. In reflecting this aggression however, the literary text leads it back to itself and accepts responsibility for it.